La résolution 688 (1991) du Conseil de Sécurité : quel devoir d'ingérence? - Carpentier, Chantal (Études internationales, 1992)
It has been said that Resolution 688 (1991) established a "right to interfere" for humanitarian reasons. This right - reference was even made to a "duty of humanitarian interference" - would allow third-party states to take the initiative of committing acts of humanitarian intervention on behalf of minorities subjected to ill treatment by the authorities of their country. Resolution 688 (1991), however, does not establish this right. Although the Security Council recognized itself as being competent to intervene, it did so because it had succeeded in identifying a threat to peace. Furthermore, although the United States, France, and Great Britain intervened, they were able to do so because they had breathed new life into humanitarian-motivated intervention by giving it the form of a sanction-intervention.